DAMPAK KEBIJAKAN PAJAK TERHADAP OPERASIONAL DAN LABA PERUSAHAAN (Studi Kasus CV Hiray Kota Parepare) - Yudistira Pratama Abbas; Bahruddin Bahruddin; Fajar Ladung; Sariana Damis (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims to determine the impact of tax policies implemented by the government on the operational activities and net profit of CV Hiray, a company engaged in the food and beverage business in Parepare City. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews with five informants, namely the leader, operational director, financial manager, and back office staff, and cashiers of CV Hiray.The results of the study indicate that tax policies, both in the form of changes in rates and digital administration obligations, have a direct impact on the company's operational system. The increase in the tax burden encourages companies to carry out cost efficiency and strategic adjustments so that operations continue to run optimally. On the other hand, tax policies also have an impact on net profit, where increases in rates or elimination of incentives reduce profit margins, while tax incentives can improve the company's financial condition. tax policies have a significant impact on the sustainability of the company's operations and finances. Therefore, an adaptive managerial strategy and careful tax planning are needed so that the company can survive and grow amidst the dynamics of fiscal regulation